Short-term effects of sweetened acidic beverages consumption on human saliva: Colloidal properties and protein composition - Samina Zaheer; Ben Kew; Chris Louca; Sassan Hafizi; Anwesha Sarkar; Mahdi Mutahar (PLoS ONE, 2025)
This study investigates the impact of a sweetened acidic beverage, an apple juice (J) consumption on the tribological properties, viscoelasticity, and protein concentration/ composition of human saliva. Using a combination of tribological measurements, quartz crystal microbalance with dissipation monitoring (QCM-D), and protein analysis, we assessed how J may affect saliva’s lubricating behaviour and adsorbed salivary film characteristics compared to water (control). Tribological results revealed that saliva (collected from 32 healthy adults) exposed to water or J exhibited increased friction when compared to unstimulated whole mouth saliva (uWMS), particularly within the boundary lubrication regime. A one-min rinse with water or J caused salivary delubrication, with water having a greater delubricating effect (p < 0.05) than that of J. Strikingly, the friction coefficients reverted to those for uWMS after 10 min (p > 0.05) highlighting the transient nature of delubrication caused by J consumption. This transient phenomenon was also evident in QCM-D measurements, where J transformed the ex vivo salivary film into a rigid layer, which reverted upon buffer application on model hydrophilic surfaces. Analysis of total protein concentration (TPC) showed that water significantly reduced TPC after one min, while J required 10 min to achieve similar TPC reduction. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) revealed that salivary cystatins and carbonic anhydrase significantly changed after J intervention, unlike water. This study highlights limited effects of J on salivary delubrication and adsorption. Building upon our findings, future research should investigate how repeated exposure to sweetened acidic beverages influences in vivo salivary pellicle dynamics and impacts to oral health.